Comparative Study of Technology Utilization in National Examinations in Malaysia and Indonesia - Supianto, Supianto; Marmoah, Sri; Indrastoeti Siti Poerwanti, Jenny; Istiyati, Siti; Mahfud, Hasan; Sukarno, Sukarno (JETL (Journal of Education, Teaching and Learning), 2024)
This study analyzes the role of technology in the national examination system in Malaysia and Indonesia, focusing on comparing the use of technology and its implications. The research method uses comparative analysis based on secondary data from various reliable sources. The data were analyzed regarding six indicators: the rate of adoption of computer-based technology, the rate of adoption of online exams, the efficiency of exam implementation, the availability of infrastructure, the use of software, and technical readiness. The results showed significant differences in the rate of adoption and utilization of technology in the national exams in the two countries. Malaysia is more advanced in adopting technology with computer-based and online exams, while Indonesia still struggles to equalize the necessary infrastructure. The use of technology in the national exams in Malaysia has increased efficiency and accuracy, while in Indonesia, limited infrastructure is an obstacle. This research concludes that technology can improve the quality and efficiency of national exams. Still, technical and infrastructural challenges need to be overcome so that the benefits of technology can be felt equally in both countries.